How people learn in an asynchronous online learning environment: The relationships between graduate students’ learning strategies and learning satisfaction | Comment apprennent les gens dans un environnement d’apprentissage en ligne asynchrone - Beomkyu Choi (Canadian Journal of Learning and Technology, 2016)
The purpose of this study was to examine the relationships between learners’ learning strategies and learning satisfaction in an asynchronous online learning environment, in an attempt to shed some light on how people learn in an online learning environment. One hundred and sixteen graduate students who were taking online learning courses participated in this study. The result revealed that ‘metacognitive strategy’ and ‘time and study environment’ had positive correlations with learners’ satisfaction, while ‘help seeking’ had a negative correlation. The findings of a multiple regression analysis showed that ‘metacognitive strategy’ and ‘peer learning’ led to learners’ satisfaction in an online learning environment. The findings of this study contribute to a better understanding of how successful learning occurs in an online learning environment, and provide recommendations on designing an effective online learning.